Examination of eating attitudes and symptoms of orthorexia nervosa in adolescents with and without celiac disease - Hacer Gizem Gercek; Selin Ayse İpek Bas; Aziz Kara; Aysegul Bukulmez (Journal of Eating Disorders)
Abstract Introduction Celiac disease (CD) is an autoimmune disorder triggered by gluten, leading to digestive issues, malabsorption, nutritional deficiencies, mental health effects, and long-term health risks. Previous studies have indicated that increased attention directed to food in CD treated with a gluten-free diet may increase the risk of eating disorders (ED). Although Orthorexia Nervosa (ON), defined as an obsession with healthy eating, is not yet considered an ED in an official diagnostic system, it is similar to ED in some of its features. ON in adolescents with CD has not been explored in the existing literature. We aimed to compare ON symptoms, eating attitudes, anxiety, depression, and obsessive-compulsive disorder (OCD) symptoms between adolescents with and without CD in this study. Method The study involved 30 adolescents with CD and 30 healthy controls. Participants were assessed using the Kiddie Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime version (K-SADS-PL) in a semi-structured clinical interview. The risk of ON was evaluated with the ORTO-11 questionnaire while eating attitudes were measured using the Eating Attitudes Test (EAT-40). Anxiety, depression, and OCD symptoms were compared between the adolescents with and without CD using the parent and child forms of the Revised Child Anxiety and Depression Scale (RCADS). Results ON symptoms and impaired eating attitudes were higher in adolescents with CD than in the healthy control group. No significant differences were found between the groups in terms of anxiety, depression, and OCD symptoms. In the correlation analysis of the RCADS-child form with other scales, there was a positive correlation between ON symptoms, impaired eating attitudes, and OCD symptoms. When the correlation analysis of the RCADS-parent form with other scales was examined, no significant correlation was found. Conclusion To the best of our knowledge, our study is the first to evaluate ON in adolescents diagnosed with CD, and our results show that there is an increase in the frequency of ON and impaired eating attitudes in CD. Additionally, we found that the increase in OCD symptoms in adolescents with CD was associated with ON and impaired eating attitudes.